Design study of a fast spectrum zero-power reactor dedicated to source driven sub-critical experiments - Mercatali, L.; Serikov, A.; Baeten, P.; Uyttenhove, W.; Lafuente, A.; Teles, P. (Energy conversion and management, 2010)
In the framework of the European P&T program (IFP6-EUROTRANS), the Generation of Uninterrupted Intense NEutrons pulses at the lead VEnus REactor (GUINEVERE) project consists of an Accelerator Driven System (ADS) that is composed by a fast lead simulated-cooled reactor operated in sub-critical conditions, coupled with an updated version of the GENEPI neutron generator previously used for the MUSE experiments. The GUINEVERE facility aims at developing and improving different techniques for the reactivity monitoring of sub-critical ADS’s. As such, the GUINEVERE project will comprise a series of major experiments that will be performed in the near future. The GUINEVERE facility will be located at the VENUS light water moderated research reactor at the SCK-CEN site of Mol (Belgium), which needs to be modified in order to accommodate a completely different and new type of core. A series of constraints were taken into account in the technical design of the GUINEVERE core, in order to properly conjugate the technical feasibility of this facility and the necessity to comply with the envisioned experimental program and its associated scientific outcome. The complete design study of the GUINEVERE core is the subject of this paper. The final design of the fuel assemblies, safety and control rods is provided. Also, the critical core configuration, to be used as reference for absolute reactivity measurements, is presented along with its associated reactor physics parameters, calculated by means of Monte Carlo methodologies. Finally, for licensing purposes, the GUINEVERE facility must satisfy the required nuclear safety criteria of the Belgian safety authorities, and in this paper, an overview of the safety analysis that has been performed with regard to the core physics, thermal assessment and shielding issues is also provided.